Mendelian randomization studies on the causal relationship between insomnia and disease - Hou, Xuan; Wei, Yingjun; Wang, Yongfeng; Wang, Lijun (Frontiers in Medicine, 2026)
Insomnia, a prevalent sleep disorder, poses significant threats to both physical and mental health. Traditional studies suggest multiple factors are associated with insomnia, yet the causal direction often remains unclear and susceptible to confounding biases. Mendelian randomization, a cutting-edge method leveraging genetic instrumental variables for causal inference, effectively overcomes these limitations by providing high-quality evidence to clarify causal relationships between insomnia and various diseases. This review systematically integrates 105 recent Mendelian randomization studies on insomnia. Evidence indicates that insomnia exerts clear causal effects on multiple diseases, though the strength of these associations and the robustness of evidence vary by disease type. Insomnia is a robust risk factor for coronary heart disease, anxiety-depressive disorders, type 2 diabetes, and chronic pain. Causal relationships with osteoarthritis and lung cancer are also supported, though effect sizes are relatively small. Conversely, associations with Alzheimer’s disease and schizophrenia remain unconfirmed. The studies establish a dominant causal direction from “insomnia → disease,” effectively correcting potential reverse causality bias in observational research. These findings reposition insomnia from a common symptom to a key modifiable cause of a range of psychosomatic disorders. Causal inferences grounded in genetic evidence provide a robust scientific foundation for early identification of high-risk populations, precision prevention targeting insomnia, and cross-system comorbid management.